Location and reactivity of extra-framework cation in the alkali exchanged LTL zeolites: A periodic density functional study - Jittima Meeprasert (2018)
Locations and reactivity of extra-framework alkali cations, Li+, Na+and K+, in LTL zeolite framework have been investigated by the periodic density functional theory (DFT). The relative stability of six different cation sites, A-F, was systematically studied for all AIs. The calculated results show that the energetically preferable sites for these alkali cations locate inside the cancrinite cage (B), at the center of the nonplanar 8-membered ring (MR) window (C), and at the edge of the nonplanar 8-MR window connected with the 12-MR windows (D). Among the three stable cation sites, only site D is able to directly interact with a CO molecule. The calculated adsorption energy and the C-O stretching frequency decrease when the cation size decreases. The adsorptions of CO on mono-, di-, and nona-cation systems (Si/Al = 35, 17, and 3, respectively) are not significantly different because of the large pore size of LTL zeolite and the small occupancy of the adsorbate. In addition, the photonic antenna prototype system representing by proflavine dye-zeolite L has been simulated to investigate the orientation of the adsorbed dye inside the channel of zeolite host. Proflavine dye interacts with K cation locating at the D site, the adsorbed dye is found to be slightly bent and aligned in parallel with the channel of LTL zeolite. This causes changes of photophysical properties of the adsorbed dye compared with its gas phase. © 2014 Elsevier Inc. All rights reserved.